Neuronal Networks: Interactions between Primary Neurons and Graphene Films with Different Structure and Electrical Conductivity (Adv. Funct. Mater. 11/2021). (10th March 2021) - Capasso, Andrea; Rodrigues, João; Moschetta, Matteo; Buonocore, Francesco; Faggio, Giuliana; Messina, Giacomo; Kim, Min Jung; Kwon, Junyoung; Placidi, Ernesto; Benfenati, Fabio; Bramini, Mattia; Lee, Gwan‐Hyoung; et al.
Abstract : In article number 2005300, Andrea Capasso, Giuliana Faggio, and co‐workers study the influence of graphene films with different structures on the growth and maturation of primary cortical neurons. The results suggest that high electrical conductivity by itself is not the key requirement for an efficient neuronal interface, while other physical‐chemical characteristics, such as the atomic structure, need to be considered.